Attitudes of sports coaches toward deafness as an indicator of creating an inclusive climate - Karić, Jasmina; Kordić, Milena (Specijalna edukacija i rehabilitacija, 2022)
Introduction. An inclusive approach to sports means opening up opportunities for deaf people to participate in sports activities equally to the hearing population. The paper deals with attitudes toward deafness from the perspective of sports coaches, who represent an important factor in creating an inclusive sports environment. Objectives. The aim of this research was to determine the orientation of sports coaches’ attitudes toward deafness. As part of the research tasks, attitudes were examined in relation to age, gender, level of education and the type of sport the coaches practice. Methods. The research was conducted on a sample of 39 participants within the population of sports coaches. The sample consisted mostly of male subjects (66.7 %) 24 to 60 years of age, with the average age being 30.8 (SD = 7.61). Most participants completed undergraduate academic studies (43.6%). The majority of the sample were team sports coaches (82.1%). The Attitudes to Deafness Scale was used as an instrument. Results. The results showed that sports coaches were neutral in their attitudes toward deafness. Age, gender, level of education, and the type of sport did not appear to be significant factors in their attitudes toward deafness. Conclusion. Future research can focus on tests that will test the presence and influence of joint contact between sports coaches and deaf people on their attitudes toward deafness. The dominance of neutral and negative attitudes potentially represents an obstacle to the social inclusion of the deaf through sports and challenges experts dealing with the deaf population to subtly influence the change of attitudes of sports coaches toward deafness in adequate ways.
Keywords: deafness; social inclusion; attitudes; sports coaches